Sleep features in menopausal women (literature review) - I. M. Madaeva; N. V. Semenova; V. A. Astafyev; E. B. Druzhinina; A. V. Labygina (Acta Biomedica Scientifica)
The article reviews the literature of domestic and foreign researchers devoted to the somnological aspects of the menopausal period in women. Age-related changes in the structural organization of sleep are shown with a deficiency of sex steroids, also and in the gender aspect. A high frequency of sleep disorders in menopausal women, reaching 60 %, has been revealed. However, the results of studies on complaints of sleep disorders depending on the climacteric phase are ambiguous, which may be due to ethnicity. Data on some pathogenetic mechanisms of the formation of the most frequent sleep disorders in menopausal women - insomnia, obstructive sleep apnea syndrome and fibromyalgia - are described. The results of polysomnography in these pathological states are presented, indicating a decrease in sleep efficiency, a change in its "architecture", and a longer waking time during the night with insomnia; a significant increase in the apnea/hypopnea index, a delay in the phase of fast sleep, a decrease in the duration of deep stages of sleep and a decrease in its effectiveness - in obstructive sleep apnea syndrome. The social and medical consequences of sleep disorders and their comorbidity with such pathological conditions as mental disorders, obesity, cardiovascular diseases, oncology, disorders of carbohydrate metabolism, bronchial asthma, mortality are noted.